Abordagens pedagógicas no ensino da ortóptica e ciências da visão na ESTeSL - Lança, Carla Costa (2018)
Digital strategy in higher education institutions: advances in knowledge have resulted in an increasing use of technology for personal and educational purposes; online learning is the delivery of a learning, training or education program by electronic means; a range of online learning management system software is available for educators such as Moodle, Blackboard, and Canvas; the use of online learning is growing in medical education. Digital strategy IN the BSc Orthoptic degree: in 2011, online learning activities were introduced in the teaching of the research in orthoptics module for final year undergraduate orthoptic students (4-year program) at ESTeSL. A research study undertaken at ESTeSL (n=42) from 2012/13, 2013/14 and 2016/17 cohorts showed that the majority of the students used the Moodle platform only to submit and download learning materials. Conclusions: Rating the tutor support higher than peer support could reflect that the students are still very dependent on the lecturer. Although e-learning is an effective approach in many medical schools, it should not replace traditional learning.